Differences In Knowledge About Hiv/ Aids And Perceived Exposure To Risk Between Physicians And Nurses In Ibadan Nigeria (2001)
Knowledge of health care providers in the management of their patients, particularly those with HIV/ AIDS is very vital, yet studies evaluating this are still seriously in dearth despite the Nigerian peculiarity to the AIDS scourge. Two hundred and ten (210) physicians and nurses working with the University College Hospital Ibadan, Nigeria were assessed with a questionnaire, which tapped information about their knowledge on HIV/ AIDS as well as their perceived exposure risk. Results showed that both the physicians and nurses have substantial overall knowledge about HIV/ AIDS. However, a significant difference existed between physician and nurses regarding the following items: more physicians than nurses believed that HIV/ AIDS is an infectious disorder (x2 = 6.67; P < .03); and more nurses than physicians agreed that coming in contact with unsterilized equipment such as needles, blades can spread HIV/ AIDS (x2 = 22.3; P< .000). There was however no significant differences in their perceived exposure to risk across each of the statements assessed. The result suggests that both physicians and nurses are comparable in relation to their knowledge and perceived exposure risk to HIV/ AIDS patients and their treatment procedure. It is therefore recommended that the assessment and evaluation of knowledge about HIV/ AIDS of physicians and nurses should be a continuous exercise for the identification of their training needs, and in the improvement of the quality of life of patients with AIDS (PWA).